2019
DOI: 10.18806/tesl.v36i3.1327
|View full text |Cite
|
Sign up to set email alerts
|

A Reflective Approach to Digital Technology Implementation in Language Teaching: Expanding Pedagogical Capacity by Rethinking Substitution, Augmentation, Modification, and Redefinition

Abstract: As the number of language instructors seeking to implement digital technologies in their teaching continues to grow, so does the need for direction with regard to making pedagogically sound decisions concerning digital tool use. One popular and useful guide for considering the educational potential of digital technologies has been Puentedura’s (2006) Substitution-Augmentation-Modification-Redefinition (SAMR) model, with its four levels of progressive technological integration. However, the degree of technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…Using the ADDIE model, the AROLS was designed and developed to create additional effects to augment the traditional 2D picture book. After implementation and evaluation, the significant preversus post-test results proved that the AROLS not only achieved comparable effects to the 2D picture book approach, it also successfully achieved augmentation effects based on the SAMR model [6], thereby enhancing target learners' knowledge acquisition about oysters.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using the ADDIE model, the AROLS was designed and developed to create additional effects to augment the traditional 2D picture book. After implementation and evaluation, the significant preversus post-test results proved that the AROLS not only achieved comparable effects to the 2D picture book approach, it also successfully achieved augmentation effects based on the SAMR model [6], thereby enhancing target learners' knowledge acquisition about oysters.…”
Section: Discussionmentioning
confidence: 98%
“…This study adopted the Substitution-Augmentation-Modification-Redefinition Model [6,7] as the framework to apply technology in the marine education curriculum at the target primary school (See Figure 1). Specifically, the Enhancement stage of the framework was realized by the AROLS.…”
Section: Theoretical Framework For the Studymentioning
confidence: 99%
“…Therefore, as many educators continue to evolve in their online instructional repertoire, intentionality must be considered essential to enhancing online instruction. Lyddon ( 2019 ) suggests technology integration is determined by a variety of complex factors which are “generally unconscious” and are largely ignored (p. 186)—this seems especially true when the goal for many educators during emergency remote teaching was simply to “convert” preexisting lessons. Thus, it may be powerful to encourage educators to revisit their personal beliefs about teaching and learning and share their stories (Cardinal et al, 2021 )—with a goal of increased intentionality for improved remote instruction.…”
Section: Discussion: “We Are Still Putting Out Fires”: Considering Intentionalitymentioning
confidence: 99%
“…Hence, it has become a necessity to prepare prospective teachers to acquire good command of applying technology in their teaching practices. It is no longer a question whether it is effective to apply technology in teaching practices, but how (Lyddon, 2019). It was reported by the UNESCO (2017) that there are approximately 264 million individuals (kids and adolescents) who cannot attend regular schools.…”
Section: Samr Modelmentioning
confidence: 99%
“…It relies on applying higher levels of technological tools to capture the attention and interest of PTs during teaching programs. Lyddon (2019) has indicated that SAMR model is characterized by its practical appeal, simplicity and modernized instructional techniques. In spite of the existence of some studies that dealt with the three variables of the research, very little if any empirical research exists on the relationship between dialogic teaching approach, SAMR model and reflective teaching skills.…”
Section: Introductionmentioning
confidence: 99%